Cotton aphid feeding preference and the development of watermelon plants treated with silicon - Pereira, Rosane Rodrigues da Costa; Leite, Mara Pestana; Silva, Douglas Marcelo Pinheiro da; Zaché, Ronelza Rodrigues da Costa; Pereira, Carlos Eduardo (Revista de Ciências Agroveterinárias, 2021)
The cotton aphid is one of the main watermelon crop pests and may cause a reduction in productivity due to the suction of sap, the transmission of viruses, and decreased photosynthetic capacity. The objective of this research was to evaluate the feeding preference of the aphid Aphis gossypii and the biometric aspects of watermelon cultivar plants submitted to silicon application. The experiment was conducted at the Institute of Education, Agriculture, and Environment of the Federal University of Amazonas, in Humaitá, Brazil. A randomized complete block design was used for testing preference with choice and a completely randomized design to study the biometric parameters of the plants. The treatments were distributed in a 2 x 3 factorial scheme (with and without silicon and considering cultivars Crimson Sweet, Fairfax, and Charleston). Silicic acid was applied at a 1% concentration directly on the substrate around the plants (equivalent to 1 t SiO2 ha-1), 25 days after sowing. The aphids in the breeding were kept in cucumber plants of cultivar Caipira. The treatments were evaluated through the preference test on watermelon cultivars and biometric studies of plant growth and development. The data were submitted to an analysis of variance, and the means were compared using the F and Scott-Knott tests at the 5% probability level. Silicon does not affect the preference of Aphis gossypii in different watermelon cultivars and negatively affects plant growth and development.